2015
DOI: 10.1158/1541-7786.mcr-14-0163
|View full text |Cite
|
Sign up to set email alerts
|

CDK2 Transcriptional Repression Is an Essential Effector in p53-Dependent Cellular Senescence—Implications for Therapeutic Intervention

Abstract: Cellular senescence, a form of cell-cycle arrest, is a tumorsuppressor mechanism triggered by multiple tumor-promoting insults, including oncogenic stress and DNA damage. The role of cyclin-dependent kinase 2 (CDK2) regulation has been evaluated in models of replicative senescence, but little is known regarding its role in other senescence settings. Using in vitro and in vivo models of DNA damage-and oncogene-induced cellular senescence, it was determined that activation of the tumor-suppressor protein p53 (TP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 39 publications
0
23
1
Order By: Relevance
“…While CDK2 necessity in G1/S checkpoint control and its possible compensation for by analogs such as CDK1 were discussed [39][40][41], more recent results suggest that CDK2 is actually required for properly timed cell-cycle progression [42], which implies that a downregulation of this protein would theoretically lead to an increased number of cells in the G1 phase. Additionally, CDK2 was also proposed as an actor in G2 cell-cycle arrest after exposure to 2 µM OTA due to its role in cell senescence [43,44]. However, we observed that the G2 cell-cycle arrest induced by high concentrations of OTA was not influenced after CDK2 overexpression, which goes against the idea of CDK2 being a regulator of this process.…”
Section: Discussioncontrasting
confidence: 69%
“…While CDK2 necessity in G1/S checkpoint control and its possible compensation for by analogs such as CDK1 were discussed [39][40][41], more recent results suggest that CDK2 is actually required for properly timed cell-cycle progression [42], which implies that a downregulation of this protein would theoretically lead to an increased number of cells in the G1 phase. Additionally, CDK2 was also proposed as an actor in G2 cell-cycle arrest after exposure to 2 µM OTA due to its role in cell senescence [43,44]. However, we observed that the G2 cell-cycle arrest induced by high concentrations of OTA was not influenced after CDK2 overexpression, which goes against the idea of CDK2 being a regulator of this process.…”
Section: Discussioncontrasting
confidence: 69%
“…CDK2 is a vital regulator of S-phase progression and has been regarded as an anticancer drug target in several studies [ 30 , 31 ]. Recent studies show that for both DNA damage- and oncogene-induced cellular senescence, CDK2 transcript and protein are inhibited in a p53- and RB-dependent manner, and this repression is necessary for cell cycle exit during senescence, suggesting that there may exist a potential relationship between TP53 and CDK2 [ 32 ]. Limited by few studies about the relationship between TP53 and CDK2 in glioma, further research is necessary to clarify the underlying correlation and mechanism between TP53 and CDK2.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, attention is increasingly being focused on cell cycle, as a potential target for therapeutic intervention [35, 57, 58]. In this context, our finding that aspirin and salicylic acid down-regulate cyclin A2 /CDK2 protein and mRNAs in multiple cancer cell lines should initiate new thinking and research on these age-old drugs in cancer treatment.…”
Section: Discussionmentioning
confidence: 99%